2021
DOI: 10.3390/ijerph18062888
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Supported HBO Therapy in Femoral Head Necrosis: A Systematic Review and Meta-Analysis

Abstract: Although many studies have shown that hyperbaric oxygen (HBO) therapy can significantly improve symptoms and quality of life of patients affected by femoral head necrosis, this therapy is not worldwide approved yet. This meta-analysis was performed to evaluate its clinical effect. Relevant studies published before May 2020 were systematically searched using terms related to HBO and femoral head necrosis. Fixed and random-effects models were used to estimate the odds ratio (OR) with 95% confidence intervals (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 111 publications
0
27
0
1
Order By: Relevance
“…G. Finally HBOT can significantly improve symptoms and quality of life of patients affected by femoral head necrosis (ECHM recommendation type II level of evidence B) [ 123 ] as well as the previously mentioned NSTI, gas gangrene and urgent HBO alpha toxin neutralized…”
Section: Approved Indications For Hbotmentioning
confidence: 99%
“…G. Finally HBOT can significantly improve symptoms and quality of life of patients affected by femoral head necrosis (ECHM recommendation type II level of evidence B) [ 123 ] as well as the previously mentioned NSTI, gas gangrene and urgent HBO alpha toxin neutralized…”
Section: Approved Indications For Hbotmentioning
confidence: 99%
“…HBO therapy has been suggested to be an effective option for patients with early‐stage ON 205 . A recent meta‐analysis for 10 studies using HBO therapy as the treatment for ON has identified a significant clinical benefit of HBO therapy on ON in Asian populations 206 . It is necessary to clarify the effect of hyperbaric oxygen therapy on glucocorticoid‐induced ON in the future.…”
Section: Glucocorticoid‐induced Osteonecrosis Animal Modelsmentioning
confidence: 99%
“…HBO has proved to be highly effective against early stages of femoral head necrosis, particularly in Asian populations (52)(53)(54)(55). In a recent study (56) on 19 patients with stage II ONFH, 12 (52.2%) underwent core decompression (CD) surgery and 11 (47.8%) received HBO treatment.…”
Section: Hyperbaric Oxygen Therapy (Hbo)mentioning
confidence: 99%
“…However, 8 patients (34.7%) progressed to a higher radiological stage during the first year of follow-up and the progression rate was similar in both groups. Studies have also shown that HBO therapy is as effective as CD for treating non-traumatic pre-collapsed femoral head AVN and therefore can be used a non-invasive alternative (52)(53)(54)(55)(56). The clinical efficacy of HBO depends on the synthesis of growth factors, which promote wound healing and reduce post-ischemia and post-inflammatory damage (57,58).…”
Section: Hyperbaric Oxygen Therapy (Hbo)mentioning
confidence: 99%